2005
DOI: 10.1152/ajpheart.01270.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of capillary hydraulic conductivity in response to an acute change in shear

Abstract: -The effects of mechanical perturbations (shear stress, pressure) on microvascular permeability primarily have been examined in micropipette-cannulated vessels or in endothelial monolayers in vitro. The objective of this study is to determine whether acute changes in blood flow shear stress might influence measurements of hydraulic conductivity (Lp) in autoperfused microvessels in vivo. Rat mesenteric microvessels were observed via intravital microscopy. Occlusion of a third-order arteriole with a micropipette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
8
29
0
Order By: Relevance
“…In situ studies indicate that capillary L p correlates with relative change in τ in mesenteric capillaries of frog (Williams, 1999) and rat (Kim et al, 2005). Consistent with the culture and capillary data are reports from whole organ preparations where permeability to surface area product increased with changes in flow (Rippe et al, 1978), red blood velocity in skeletal muscle capillaries correlated with permeability to Cr-EDTA (Shibata and Kamiya, 1992), and capillary filtration coefficient rose rapidly with exercise (Björnberg, 1990).…”
Section: Introductionsupporting
confidence: 75%
“…In situ studies indicate that capillary L p correlates with relative change in τ in mesenteric capillaries of frog (Williams, 1999) and rat (Kim et al, 2005). Consistent with the culture and capillary data are reports from whole organ preparations where permeability to surface area product increased with changes in flow (Rippe et al, 1978), red blood velocity in skeletal muscle capillaries correlated with permeability to Cr-EDTA (Shibata and Kamiya, 1992), and capillary filtration coefficient rose rapidly with exercise (Björnberg, 1990).…”
Section: Introductionsupporting
confidence: 75%
“…These findings are consistent with others showing shear stress-mediated endothelial morphological adaptations 22,38,[49][50][51][52] and permeability. 14,17,19,21,23,53 The presence of tumor cells also increased P d relative to endothelial mono-cultures, with a significantly greater P d under high WSS conditions. Images taken at the end of the permeability assay for the case of t W D 10 dyn/ cm 2 qualitatively show greater distribution of dextran across the endothelium during co-culture with tumor cells, relative to dextran distribution immediately post 72 hrs preconditioning (Fig.…”
Section: Endothelial Barrier Functionmentioning
confidence: 94%
“…Many reports have documented the effect of wall shear stress (WSS) on endothelial cell-matrix interactions, junction molecules, gene expression, barrier transport properties, and angiogenesis. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] For example, reports have shown that shear stress causes upregulation of Tie2 and MMP-1 25 and increases vascular endothelial growth factor (VEGF) expression in endothelial cells. 28 Similar studies have also shown that shear stress stimulates endothelial cell migration as well as supports blood vessel maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 The enhanced permeability in small vessels has been reported as a manifestation of damage to small vessels in the brain and has been proposed as an important pathogenesis of cerebral microvascular disease. 39,40 Our analysis of components of the carotid artery flow waveform only supports the aforementioned view.…”
Section: Hirata Et Al Aging Changes In Carotid Pressure and Flow 2555mentioning
confidence: 99%